DAMPAK PENGEMBANGAN EKOWISATA DI SEKSI WILAYAH III TANJUNG HARAPAN TAMAN NASIONAL TANJUNG PUTING TERHADAP SOSIAL BUDAYA MASYARAKAT DESA WISATA SEKONYER - Tesalonika Purnama Siregar; Joko Mijiarto (Journal Publicuho, 2024)
This study aims to identify and analyze these impacts using a qualitative approach. Data were collected through in-depth interview techniques, observation, and documentation. The results of the study indicate that ecotourism activities have a positive impact on the local community. First, ecotourism increases community knowledge and insight into environmental management and sustainability-based tourism potential. Second, community awareness of local natural and cultural wealth is increasing, encouraging the preservation of traditional cultural values. Third, the social status of the community increases through active participation in tourism activities. Fourth, it also has an impact on foreign language skills, especially English, as a need for interaction with tourists. Fifth, community empowerment can be seen from the emergence of new economic opportunities, such as homestay management, local crafts, and tour guide services. This study emphasizes the importance of synergy between ecotourism managers, the government, and the community to maintain long-term benefits for the sustainability of ecotourism and the welfare of the local community.